P1-S2.31 Mean streets vs main street - more street youth report STIs, multiple sexual partners and lower condom use compared to their peers in the general population. (10th July 2011) - Fang, L; Klar, S A; Tawse, C; Friedman, D; Taylor, D; Gratrix, J; Wiley, J; Wright, J; Rossi, M; Wong, T; Gayaraman, G C; ,
Abstract : Background: The burden of sexually transmitted infections (STIs) and engagement in high risk behaviours is assumed to be greater in street-involved youth (SIY) than the general population, but the magnitude of this difference has rarely been described. Methods: Preliminary data from four sites (n=734) of E-SYS cycle 6 (Enhanced Surveillance of Street Youth, 2009-present) and the corresponding metropolitan centres of CCHS 2009 (Canadian Community Health Survey) were analysed. E-SYS is a repeated cross-sectional study of SIY (15–24 years), who completed an interviewer-administered questionnaire and provided blood and urine samples for STI, HIV and HCV testing. CCHS is a representative cross-sectional over the phone survey of Canadians, which collects data on health determinants and status. The CCHS sample was restricted to youth aged 15–24 years (weighted n=708 589, unweighted n=780). Estimates of self-reported STIs, sexual behaviours, substance use and demographics are reported with 95% CIs and IQRs. Results: Compared to their peers in the general population, a greater proportion of SIY were male, between 15 and 19 years old, Aboriginal, Canadian-born, without a high school diploma and have higher rates of regular binge drinking, smoking and illicit drug use (Abstract P1-S2.31 table 1 ). A greater proportion of SIY (23.8% vs 3.5%) reported sexualities other than straight/heterosexual. A higher proportion of SIY had had sexual intercourse (95.5% vs 67.4%) and had been diagnosed with an STI (18.7% vs 3.8%). Sexually active SIY reported a lower proportion of condom use at last intercourse (35.4% vs 52.3%). The median age at first intercourse was 14 years among SIY and 17 years among youth in the general population. The median number of sexual partners for youth in the general population was one (last 12 months) compared to two partners for SIY (last 3 months). Conclusions: Street-involved youth are more vulnerable to the social determinants of health, which partly explains the marked differences between them and their peers in the general Canadian population. Lower levels of education and other structural factors, combined with higher levels of substance use and riskier sexual practices may contribute to the higher burden of STIs among SIY. The magnitude of differences between the two groups highlights the need for continued efforts using a multi-sectoral approach to address the needs of this population though targeted interventions and programs.